Peningkatan Manajemen Usaha Dan Diversifikasi Produk Usaha Rumahan Jajanan Tradisional Desa Bintoro, Kabupaten Demak - Ratna Wijayanti; Suratman ‎ ‎ ‎; Ika Fitriana (Jurnal ABM Mengabdi, 2021)
The focus of this PKM are efforts to improve business management and home industry production quality in Demak Regency. Partners are home industry business actors with various market snacks products. Based on the situation analysis, partners have problems in production aspects and business management. Problems in production are limited tools, partners use manually production. The problem in marketing is the limited marketing reach, the product is only sold in one traditional market. The problem in financial aspect are that partners do not have financial books and records so that profits or losses cannot be detected properly. The solutions offered for problems in the production aspect are Machine facilitation and workshops for Mixing Dough and Making Frozen Food Products. Solutions for marketing aspects, namely training and workshops on making product variations and packaging. Solutions for financial aspects include training in simple bookkeeping and business financial management. All of the target solutions offered have been fulfilled by the PKM team to partners. The benefits that partners get from this community service program include: (1) Increased turnover, (2) Improved Machine Use Skills, (3) Improved Partner Understanding and Skills in Doing Simple Bookkeeping and separating family and business finances and (4) Expanding Marketing Reach